T Tinjauan Siyasah Dusturiyah Tentang Penindakan Penyelundupan Barang Berdasarkan Peraturan Direktorat Jenderal Bea dan Cukai Nomor P-53/Bc/2010 di Kota Bandung - Gojali, Moh Aziz; Sutiana, Yana; Tresnayadi, Budi (FISIP UIN SGD Bandung, 2025)
This study aims to critically examine the effectiveness of law enforcement efforts against illegal goods smuggling conducted by the Directorate General of Customs and Excise in Bandung City, based on Regulation No. P-53/BC/2010, through the normative lens of Siyasah Dusturiyah in Islamic political theory. Employing a qualitative juridical-empirical method, this research integrates doctrinal legal analysis with field data obtained through interviews, document studies, and observations. The findings reveal persistent structural and operational challenges, including limited technological surveillance, insufficient human resources, weak inter-agency coordination, and low public legal awareness. These issues have contributed to the continued rise in smuggling activities, indicating gaps in the current enforcement framework. From the perspective of Siyasah Dusturiyah, smuggling is not merely a violation of state law but a transgression against public welfare (maslahah ‘ammah), undermining economic justice and societal harmony. The study concludes that an integrated enforcement strategy—combining preventive, repressive, and rehabilitative approaches—is essential to address the root causes of smuggling. Furthermore, the research contributes theoretically by reinforcing Siyasah Dusturiyah as a moral and legal framework for customs governance, and practically by advocating for a participatory and ethically grounded legal culture. This holistic model is vital for developing an accountable, just, and spiritually conscious enforcement system in the face of transnational economic threats. Contribution: By situating smuggling as not only a legal violation but also a breach of public welfare and economic justice from an Islamic political perspective, the research advances the discourse on integrating moral and spiritual values into state governance.